Synthesis, characterization and application of composite derived from rice husk ash with aluminium oxide for sorption of uranium - W. M. Youssef; M. S. Hagag; A. H. Ali (Adsorption Science & Technology)
A composite of rice husk (RH), caustic soda and aluminium oxide was synthesized at 500°C. The activated carbon and amorphous silica dispersed over the aluminium oxide selectively adsorbed uranium in the presence of other elements. At equilibrium time 1 h, phase ratio S/L (0.1 g/10 ml), pH = 5 and uranium initial concentration 120.6 mg/l uranium adsorption efficiency was 96.35%. The uranium stripping efficiency from the load RHA–alumina composite fulfilled 99.9% at 1 h equilibrium time, a phase ratio (S/A) of 0.05 g/10 ml and 0.5 mol/l HNO 3 . The scanning electron microscopy photos revealed that the rice husk ash (RHA)–alumina composite has vacant or regular cavities before the adsorption, and the cavities are fully occupied by uranium after adsorption. The Fourier transform infrared spectroscopy shows a more broadening of the band υ = 3526 and 3462 cm −1 which was ascribed to the uranium adsorption. The composite adsorbed 93.75% of uranium from a waste sample. The uranium adsorption exhibited a Langmuir isotherm.